Measuring Financial Access around the World - Kendall, Jake; Mylenko, Nataliya; Ponce, Alejandro (2012)
This paper introduces a new set of financial access indicators for 139 countries across the globe and describes the results of a preliminary analysis of this data set. The new data set builds on previous work using a similar methodology. The new data set features broader country coverage and greater disaggregation by type of financial product and by type of institution supplying the product -- commercial banks, specialized state run savings and development banks, banks with mutual ownership structure (such as cooperatives), and microfinance institutions. The authors use the data set to conduct a rough estimation of the number of bank accounts in the world (6.2 billion) as well as the number of banked and unbanked individuals. In developed countries, they estimate 3.2 accounts per adult and 81 percent of adults banked. By contrast, in developing countries, they estimate only 0.9 accounts per adult and 28 percent banked. In regression analysis, they find that measures of development and physical infrastructure are positively associated with the indicators of deposit account, loan, and branch penetration.